EDP audit & controls ' : a better realization of EDP audit & control in Malaysia - Seminar on EDP Audit & Controls 'a Better Realization of EDP Audit & Control in Malaysia (1992 : Kuala Lumpur) ([s.l.] : [s.n.])
Keynote address/Y Bhg Tan Sri Ishak Tadin -- A survey of EDP auditing, controls & security in Malaysia/Ros Alinda Alias,Habit Noh Sayid Seman, Zailani Mohamed Sidek -- Information system audit technology : trends and applications/Prof Hart J Will -- Expert system's development in computer auditing : the UTM experience/Zailani Mohamed Sidek, Zuraini Ismail, Tajaludin Sharif -- Current practices in computer auditing in Malaysia - private sector/Ong Ai Lin -- Computer auditing in public sector/Ab Rahman Mohamed -- Boundary controls in computer security/Zainab Abu Bakar, Kalsom Nasir -- Auditing and managing of computer resources/Chin Kim Leong -- Controlling end-user computing/Mohd Hasan Selamat, Mohamed Othman, Abu Talib Othman -- Disaster recovery awareness gaining management committment/Monica Holtforster